2020
DOI: 10.1002/pro.3870
|View full text |Cite
|
Sign up to set email alerts
|

Integrating structural and evolutionary data to interpret variation and pathogenicity in adapter protein complex 4

Abstract: Genetic variation in the membrane trafficking adapter protein complex 4 (AP-4) can result in pathogenic neurological phenotypes including microencephaly, spastic paraplegias, epilepsy, and other developmental defects. We lack molecular mechanisms responsible for impaired AP-4 function arising from genetic variation, because AP-4 remains poorly understood structurally. Here, we analyze patterns of AP-4 genetic evolution and conservation to identify regions that are likely important for function and thus more su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In a large cohort, our functional assay used in combination with variant location and in silico prediction scores may provide an opportunity to further refine the impact of missense variants, aid the interpretation and classification of variants and enable further exploration of differences between subunits and functional domains in combination with structural biology approaches. 31 This could be done post hoc focusing on missense variants identified in individuals through molecular testing or prospectively using a massive parallel screen of all possible missense variants, as has been recently shown for a cancer predisposition gene. 61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort, our functional assay used in combination with variant location and in silico prediction scores may provide an opportunity to further refine the impact of missense variants, aid the interpretation and classification of variants and enable further exploration of differences between subunits and functional domains in combination with structural biology approaches. 31 This could be done post hoc focusing on missense variants identified in individuals through molecular testing or prospectively using a massive parallel screen of all possible missense variants, as has been recently shown for a cancer predisposition gene. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Next, the available domain information from UniProt 29 and pfam 30 were compared with the homology model of the AP-4 complex reported recently. 31 Domains predicted by pfam showed a greater overlap and were thus chosen for further analyses. For AP4S1, alignment was transferred from isoform 1 and isoform 2 of Q9Y6B7 using InterPro.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that the C‐terminus of the σ2 subunit plays a crucial role in AP‐2, a similar AP family protein to AP‐4, because it is the portion of the protein that associates intimately and extensively within the elbow of the α subunit (Collins et al, 2002; Kelly et al, 2008). This heterodimer structure is critical for maintaining solubility of the protein because of the highly hydrophobic residues buried at the interfaces of these two subunits (Gadbery et al, 2020). Our findings suggest that the ap4s1 truncation may have similarly compromised the assembly and the maintenance of the AP‐4 complex, resulting in the SPG52 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by the NOESY data that shows the I827 amino acid side chain methyl groups make numerous NOE contacts to several different surrounding hydrophobic side chains including T774, Y776, I787, F790, W791, L824, and M825 (Fig 4). The same rationale would apply to the newly published structure of the domain-swapped E6AP dimer (PDB 6TGK), as I827 is still found embedded in the monomeric hydrophobic core and is not involved in the dimerization interface [63]. This structural disruption likely induces an allosteric change that reduces the catalytic activity and leads to its subsequent aggregation.…”
Section: Plos Onementioning
confidence: 97%